Teaching Dance in Diaspora: Pedagogical Experiences in Melbourne, Australia - Jeanette Mollenhauer (Accelerando: BJMD)
A study of culturally specific dance following relocation to a novel and vastly different environment addresses issues that are salient to both migration research and dance studies. This paper addresses the situation faced by culturally specific dance groups in Melbourne, Australia, through the recently completed ‘Teaching Dance in Diaspora’ project. Ten dance groups from disparate socio-cultural backgrounds have been visited, with 13 dance teachers being interviewed. Collected data reveal the connections and collisions of experience among participating groups and individual pedagogues. All groups were amateur, but while some had their operational costs supported through fundraising efforts and/or corporate sponsorship within the diasporic community, others relied on tuition fees alone. Available choreographic and pedagogical support from respective homelands also varied: in turn, this often determined group structures and practices in Melbourne. Yet, every group maintained a remarkable program of performances at both diasporic community celebrations and regionalized multicultural festivals. Lamentably, another common factor was the experiential marginalization of the groups by government departments and arts bodies that privilege Western theatrical genres. Principally, the project reveals the nuanced and multi-faceted nature of negotiating and embodying post-relocation cultural identity through the lens of dance, both within the relevant diasporic group and to the broader populace. However, it also demonstrates the precarities faced by diasporic community dance groups in Australia.